Carbon nitride supported copper nanoparticles: light-induced electronic effect of the support for triazole synthesis. Issue 11 (November 2016) - Nandi, Debkumar; Taher, Abu; Ul Islam, Rafique; Siwal, Samarjeet; Choudhary, Meenakshi; Mallick, Kaushik
Abstract : The composite framework of graphitic carbon nitride ( g CN) supported copper nanoparticle can act as a high-performance photoreactor for the synthesis of 1, 2, 3-triazole derivatives under light irradiation in the absence of alkaline condition. The photoactivity of g CN originates from an electron transition from the valence band to the conduction band, in the presence of photon energy, and the hot electron acts as a scavenger of the terminal proton of the alkyne molecule to facilitate the formation of copper acetanilide complex. In this study, we have performed the experiment under a different photonic environment, including dark condition, and in the presence and absence of base. A comparative study was also executed using Cu-TiO2 system, as a reference material, in the support of our proposed mechanism. The recycling performance and the photocorrosion effect of the catalyst have also been reported in this study.